Correction: Identifying practitioner and researcher collaboration needs to improve ecosystem restoration in Canada - Tim Alamenciak; Nancy Shackelford; Logan Rehberg; Ash Baron; Catherine Febria; Alina Fisher; Tina Heger; Eric Higgs; Stephen Murphy; Ryan Stephenson; Bruno Travassos-Britto (Socio-Ecological Practice Research, 2026)

The Green Transition will be just – Or it won't succeed - Barbara Prainsack; Maria Patrão Neves; Nils-Eric Sahlin; Nikola Biller-Andorno; Jeroen van den Hoven; Migle Laukyte; Paweł Łuków; Fruzsina Molnar-Gabor; Thérèse Murphy; Tamar Sharon; Takis Vidalis; Mihalis Kritikos (Environmental Science & Policy, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Identifying practitioner and researcher collaboration needs to improve ecosystem restoration in Canada - Tim Alamenciak; Nancy Shackelford; Logan Rehberg; Ash Baron; Catherine Febria; Alina Fisher; Tina Heger; Eric Higgs; Stephen Murphy; Ryan Stephenson; Bruno Travassos-Britto (Socio-Ecological Practice Research, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Proceedings of the 2024 FDA-CRCG Workshop: Scientific and Regulatory Considerations for Assessment of Immunogenicity Risk for Generic Peptide and Oligonucleotide Drug Products - Jennifer K. Lee; Ha-Na Lee; Sudhir Agrawal; Joseph A. Balsamo; Andrew Clerman; Sofie Denies; Anne De Groot; Jeremy Fry; Nicolas Gaudenzio; Andrew J. Graves; Kristina E. Howard; SuJin Hwang; et al. (The AAPS Journal, 2026)

Assessing Impacts of Offshore Wind Development: An Analysis of the Minimization of Economic Exposure of the Scallop Fishery Through the Regulatory Process - Marina Chaji; Greg Ardini; Melanie Harsch; Alan Haynie; Min‐Yang Lee; Bryce McManus; Tammy Murphy; Lisa Pfeiffer; Eric Thunberg (Fisheries Oceanography, 2026)
Offshore wind energy has expanded as a source of clean energy in the United States since the first US offshore wind farm began operations off the coast of Rhode Island in 2016. The emergence of offshore wind has increased the need to manage ocean use across multiple stakeholder groups, a difficult and contentious process. We use 15 years of scallop ( Placopecten magellanicus ) fishery data to describe how offshore wind may expose one of the most valuable commercial fisheries in the United States to economic risks. Our analysis shows that the current configuration of approved offshore wind lease areas off the northeastern coast of the United States is expected to result in relatively small economic exposure for the scallop fishery. We also illustrate how the measured development process, which includes ample opportunity for stakeholder input, has mitigated exposure through minimization or avoidance by characterizing the change in impacted activity through two case studies. We find moderate to strong levels of exposure mitigation across our three scallop fleet métiers within the Central Atlantic (CA) region. In contrast, exposure mitigation was more variable in the New York Bight (NYB) region suggesting mitigation methods in the NYB are not as effective for the scallop fishery as the CA. The open development process that allowed for early stakeholder engagement has largely mitigated the potential for economic risk of offshore wind on the scallop industry by approving the siting of offshore wind development in less utilized or less productive scalloping areas.

Biogeography and hidden diversity in the coffee snake species complex Ninia atrata (Dipsadinae) from South America and the Lesser Antilles - Michael J. Jowers; Oriana C. Dempster Ortigoza; Teddy Angarita-Sierra; John C. Murphy; AmaËl Borzée; Gilson A. Rivas; Richard M. Lehtinen; Matthew J. Ingrasci; Eric N. Smith (Systematics and Biodiversity, 2025)

NCBI Orthologs: Public Resource and Scalable Method for Computing High-Precision Orthologs Across Eukaryotic Genomes - Dong-Ha Oh; Alexander Astashyn; Barbara Robbertse; Nuala A. O’leary; W. Ray Anderson; Laurie Breen; Eric Cox; Olga Ermolaeva; Robert Falk; Vichet Hem; J. Bradley Holmes; Patrick Masterson; et al. (Journal of Molecular Evolution, 2025)
Orthologs are fundamental for enabling comparative genomics analyses that further our understanding of eukaryotic biology. The unprecedented increase in the availability of high-quality eukaryotic genomes necessitates scalable and accurate methods for orthology inference. The National Center for Biotechnology Information (NCBI) developed “NCBI Orthologs”, a resource and a computational pipeline designed to meet this challenge within the NCBI RefSeq framework. This system integrates protein similarity, nucleotide alignment, and microsynteny to achieve high-precision ortholog assignments across diverse eukaryotes. The pipeline leverages high-quality RefSeq annotations and processes genomes individually, ensuring scalability. Resulting ortholog data, organized into gene-level anchored sets, enables propagation of functional annotation information and facilitates comparative genomics. Critically, these data are integrated into the NCBI Gene resource, providing users with access from various entry points. The NCBI Datasets resource provides an intuitive interface to explore orthologous relationships on the web and allows bulk data download via the web, command-line tools, and an API. We detail the methodology, including anchor species selection and the decision tree used to arrive at high-confidence one-to-one orthology relationships. NCBI Orthologs is a valuable resource for facilitating functional annotation efforts and enhancing our understanding of eukaryotic gene evolution.

Record of seismic slip in carbonates: Insights from the Venere Fault during the 1915 Avezzano earthquake (Mw 7.0), Central Italy - Nina Zamani; Sara Satolli; Michael Murphy; Francois Demory; Bruno Pace; Jérôme Gattacceca; Ján Kaňuk; Michaela Nováková; Raphael Gottardi; Eric C. Ferré (Journal of Structural Geology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Food safety assessment and 28-day toxicity study of the synbiotic medical food consortium SBD121 - D. Davidson Easson; Vincent A. Murphy; Alicia E. Ballok; Maria J. Soto-Giron; Kelsey J. Miller; Mark R. Charbonneau; Eric M. Schott; Tracy Greene; Joseph Rodricks; Gerardo V. Toledo (Food and Chemical Toxicology, 2024)

A comparison between full-length 16S rRNA Oxford nanopore sequencing and Illumina V3-V4 16S rRNA sequencing in head and neck cancer tissues - Kenny Yeo; James Connell; George Bouras; Eric Smith; William Murphy; John-Charles Hodge; Suren Krishnan; Peter-John Wormald; Rowan Valentine; Alkis James Psaltis; Sarah Vreugde; Kevin Aaron Fenix (Archives of Microbiology, 2024)
Describing the microbial community within the tumour has been a key aspect in understanding the pathophysiology of the tumour microenvironment. In head and neck cancer (HNC), most studies on tissue samples have only performed 16S rRNA short-read sequencing (SRS) on V3-V5 region. SRS is mostly limited to genus level identification. In this study, we compared full-length 16S rRNA long-read sequencing (FL-ONT) from Oxford Nanopore Technology (ONT) to V3-V4 Illumina SRS (V3V4-Illumina) in 26 HNC tumour tissues. Further validation was also performed using culture-based methods in 16 bacterial isolates obtained from 4 patients using MALDI-TOF MS. We observed similar alpha diversity indexes between FL-ONT and V3V4-Illumina. However, beta-diversity was significantly different between techniques (PERMANOVA - R 2 = 0.131, p

Short-stature and tall maize hybrids have a similar yield response to split-rate vs. pre-plant N applications, but differ in biomass and nitrogen partitioning - Kevin R. Kosola; Magen S. Eller; Frank G. Dohleman; Lia Olmedo-Pico; Brad Bernhard; Eric Winans; Ty J. Barten; Lillian Brzostowski; Lesley R. Murphy; Chiyu Gu; Lyle Ralston; Mike Hall; et al. (Field Crops Research, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Modeling Multiphase Heat and Mass Transfer in an Agitated Filter Dryer by Integrating Experiment, Computations, and Analytical Solutions - Viraj V. Belekar; Eric J. Murphy; Theodore J. Heindel; Nandkishor K. Nere; Shankar Subramaniam (Pharmaceutical Research, 2022)

Metabolism in the Midwest: research from the Midwest Aging Consortium at the 49th Annual Meeting of the American Aging Association - Michaela E. Murphy; Akilavalli Narasimhan; Alexis Adrian; Ankur Kumar; Cara L. Green; Carolina Soto-Palma; Chathurika Henpita; Christina Camell; Christopher S. Morrow; Chung-Yang Yeh; Claire E. Richardson; Cristal M. Hill; et al. (GeroScience, 2022)

A Novel Computational Approach Coupled with Machine Learning to Predict the Extent of Agglomeration in Particulate Processes - Kushal Sinha; Eric Murphy; Prashant Kumar; Kirsten A. Springer; Raimundo Ho; Nandkishor K. Nere (AAPS PharmSciTech, 2021)

Opportunities and Challenges for Including Oyster-Mediated Denitrification in Nitrogen Management Plans - Julie M. Rose; J. Stephen Gosnell; Suzanne Bricker; Mark J. Brush; Allison Colden; Lora Harris; Eric Karplus; Alix Laferriere; Nathaniel H. Merrill; Tammy B. Murphy; Joshua Reitsma; Johnny Shockley; et al. (Estuaries and Coasts, 2021)
Nitrogen pollution is one of the primary threats to coastal water quality globally, and governmental regulations and marine policy are increasingly requiring nitrogen remediation in management programs. Traditional mitigation strategies (e.g., advanced wastewater treatment) are not always enough to meet reduction goals. Novel opportunities for additional nitrogen reduction are needed to develop a portfolio of long-term solutions. Increasingly, in situ nitrogen reduction practices are providing a complementary management approach to the traditional source control and treatment, including recognition of potential contributions of coastal bivalve shellfish. While policy interest in bivalves has focused primarily on nitrogen removal via biomass harvest, bivalves can also contribute to nitrogen removal by enhancing denitrification (the microbial driven process of bioavailable nitrogen transformation to di-nitrogen gas). Recent evidence suggests that nitrogen removed via enhanced denitrification may eclipse nitrogen removal through biomass harvest alone. With a few exceptions, bivalve-enhanced denitrification has yet to be incorporated into water quality policy. Here, we focus on oysters in considering how this issue may be addressed. We discuss policy options to support expansion of oyster-mediated denitrification, describe the practical considerations for incorporation into nitrogen management, and summarize the current state of the field in accounting for denitrification in oyster habitats. When considered against alternative nitrogen control strategies, we argue that enhanced denitrification associated with oysters should be included in a full suite of nitrogen removal strategies, but with the recognition that denitrification associated with oyster habitats will not alone solve our excess nitrogen loading problem.

Not withering on the evolutionary vine: systematic revision of the Brown Vine Snake (Reptilia: Squamata: Oxybelis) from its northern distribution - Robert C. Jadin; Christopher Blair; Sarah A. Orlofske; Michael J. Jowers; Gilson A. Rivas; Laurie J. Vitt; Julie M. Ray; Eric N. Smith; John C. Murphy (Organisms Diversity & Evolution, 2020)

Perspectives on in situ Sensors for Ocean Acidification Research - Akash R. Sastri; James R. Christian; Eric P. Achterberg; Dariia Atamanchuk; Justin J. H. Buck; Philip Bresnahan; Patrick J. Duke; Wiley Evans; Stephen F. Gonski; Bruce Johnson; S. Kim Juniper; Steve Mihaly; et al. (Frontiers in Marine Science, 2019)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Erratum to: The OECD validation program of the H295R steroidogenesis assay: Phase 3. Final inter-laboratory validation study - Markus Hecker; Henner Hollert; Ralph Cooper; Anne-Marie Vinggaard; Yumi Akahori; Margaret Murphy; Christine Nellemann; Eric Higley; John Newsted; John Laskey; Angela Buckalew; Stefanie Grund; et al. (Environmental Science and Pollution Research, 2018)

Nitrogen availability alters rhizosphere processes mediating soil organic matter mineralisation - Conor J. Murphy; Elizabeth M. Baggs; Nicholas Morley; David P. Wall; Eric Paterson (Plant and Soil, 2017)

Zygote injection of CRISPR/Cas9 RNA successfully modifies the target gene without delaying blastocyst development or altering the sex ratio in pigs - Kristin M. Whitworth; Joshua A. Benne; Lee D. Spate; Stephanie L. Murphy; Melissa S. Samuel; Clifton N. Murphy; Jürgen A. Richt; Eric Walters; Randall S. Prather; Kevin D. Wells (Transgenic Research, 2017)

Mouse genome annotation by the RefSeq project - Kelly M. McGarvey; Tamara Goldfarb; Eric Cox; Catherine M. Farrell; Tripti Gupta; Vinita S. Joardar; Vamsi K. Kodali; Michael R. Murphy; Nuala A. O’Leary; Shashikant Pujar; Bhanu Rajput; Sanjida H. Rangwala; et al. (Mammalian Genome, 2015)
Complete and accurate annotation of the mouse genome is critical to the advancement of research conducted on this important model organism. The National Center for Biotechnology Information (NCBI) develops and maintains many useful resources to assist the mouse research community. In particular, the reference sequence (RefSeq) database provides high-quality annotation of multiple mouse genome assemblies using a combinatorial approach that leverages computation, manual curation, and collaboration. Implementation of this conservative and rigorous approach, which focuses on representation of only full-length and non-redundant data, produces high-quality annotation products. RefSeq records explicitly link sequences to current knowledge in a timely manner, updating public records regularly and rapidly in response to nomenclature updates, addition of new relevant publications, collaborator discussion, and user feedback. Whole genome re-annotation is also conducted at least every 12–18 months, and often more frequently in response to assembly updates or availability of informative data. This article highlights key features and advantages of RefSeq genome annotation products and presents an overview of NCBI processes to generate these data. Further discussion of NCBI’s resources highlights useful features and the best methods for accessing our data.

The OECD validation program of the H295R steroidogenesis assay: Phase 3. Final inter-laboratory validation study - Markus Hecker; Henner Hollert; Ralph Cooper; Anne Marie Vinggaard; Yumi Akahori; Margaret Murphy; Christine Nellemann; Eric Higley; John Newsted; John Laskey; Angela Buckalew; Stefanie Grund; et al. (Environmental Science and Pollution Research, 2011)

The role of α-synuclein in brain lipid metabolism: a downstream impact on brain inflammatory response - Mikhail Y. Golovko; Gwendolyn Barceló-Coblijn; Paula I. Castagnet; Susan Austin; Colin K. Combs; Eric J. Murphy (Molecular and Cellular Biochemistry, 2009)

Modulation of steroidogenesis by coastal waters and sewage effluents of Hong Kong, China, using the H295R assay - Tannia Gracia; Paul D. Jones; Eric B. Higley; Klara Hilscherova; John L. Newsted; Margaret B. Murphy; Alice K. Y. Chan; Xiaowei Zhang; Markus Hecker; Paul K. S. Lam; Rudolf S. S. Wu; John P. Giesy (Environmental Science and Pollution Research, 2008)

The New River, Virginia, muskellunge fishery: population dynamics, harvest regulation modeling, and angler attitudes - Travis O. Brenden; Eric M. Hallerman; Brian R. Murphy; John R. Copeland; Joseph A. Williams (Environmental Biology of Fishes, 2007)

Risk of adverse behavioral effects with pediatric use of antidepressants - Wayne K. Goodman; Tanya K. Murphy; Eric A. Storch (Psychopharmacology, 2007)

The OECD Validation Program of the H295R Steroidogenesis Assay for the Identification of In Vitro Inhibitors and Inducers of Testosterone and Estradiol Production. Phase 2: Inter-Laboratory Pre-Validation Studies (8 pp) - Markus Hecker; Henner Hollert; Ralph Cooper; Anne-Marie Vinggaard; Yumi Akahori; Margaret Murphy; Christine Nellemann; Eric Higley; John Newsted; Rudolph Wu; Paul Lam; John Laskey; et al. (Environmental Science and Pollution Research, 2007)

A STEPWISE METHOD FOR THE ISOLATION OF ENDOTHELIAL CELLS AND SMOOTH MUSCLE CELLS FROM INDIVIDUAL CANINE CORONARY ARTERIES - MICHAEL K. DAME; XINWEN YU; ROSARIO GARRIDO; WALTER BOBROWSKI; J. ERIC MCDUFFIE; HEDWIG S. MURPHY; MUDHER ALBASSAM; JAMES VARANI (In Vitro Cellular & Developmental Biology - Animal, 2003)

Sterol carrier protein‐2:Not just for cholesterol any more - Eric J. Murphy (Molecular and Cellular Biochemistry, 2002)

Assessment of Risks of Brodifacoum to Non-target Birds and Mammals in New Zealand - Charles T. Eason; Elaine C. Murphy; Geoffrey R.G. Wright; Eric B. Spurr (Ecotoxicology, 2002)

ATP synthesis is coupled to rat liver mitochondrial RNA synthesis - S. Fenella DasGupta; Stanley I. Rapoport; Mariana Gerschenson; Eric Murphy; Gary Fiskum; Stephen J. Russell; Krish Chandrasekaran (Molecular and Cellular Biochemistry, 2001)

Fatty acid uptake in diabetic rat adipocytes - Heather Fraser; Scott M. Coles; Judith K. Woodford; Audrey A. Frolov; Eric J. Murphy; Friedhelm Schroeder; David A. Bernlohr; Vernon Grund (Molecular and Cellular Biochemistry, 1997)